Construction of anoikis-related lncRNAs risk model: Predicts prognosis and immunotherapy response for gastric adenocarcinoma patients - Li, Qinglin; Zhang, Huangjie; Hu, Jinguo; Zhang, Lizhuo; Zhao, Aiguang; Feng, He (Frontiers in Pharmacology, 2023)
Gastric cancer (GC) is one of the most common cancers, but its pathogenesis and early diagnosis have not been fully uncovered. Gastric adenocarcinoma (STAD), the most common subtype of stomach cancer, has a very poor prognosis despite great progress in recent decades. Therefore, it is necessary to further improve the risk as-sessment of STAD distant metastasis. Anoikis acts as a programmed cell death that is activated during tumorigenesis to remove cells isolated from extracellular matrix (ECM). Anoikis acts as a programmed cell death that is activated during tumorigen-esis to remove undetected cells isolated from ECM. Further anoikis risk stratifica-tion is expected to provide a deeper understanding of the process by which GC can-cer cells separate from the extracellular matrix and undergo distant metastasis. We established a STAD prognostic model based on five anoikis associated lncRNAs (ARLs) according to the TCGA database, and subsequently tested the accuracy of the model in predicting the prognosis. We further comprehensively explored the func-tion and clinical significance of this prognostic model through clinical subgroup analysis, tumor mutation burden (TMB) detection, drug susceptibility analysis, im-mune infiltration, pathway enrichment analysis. The establishment of this model not only provides a new assessment method for the risk of distant metastasis of STAD, but also provides a new perspective for the individualized and precise treatment of STAD.